KELAYAKAN BAHAN AJAR INTERAKTIF SISTEM PERNAPASAN MANUSIA PADA KETERAMPILAN BERPIKIR KRITIS SISWA KELAS V SD - Ningsih, Herna; Rokhman , Fathur; Eko Pramono, Suwito; Joko Raharjo, Tri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Science education on the subject of the human respiratory system in fifth grade elementary school still faces a number of obstacles, including teacher-centered learning, limited interactive teaching materials, and low student participation, resulting in students' critical thinking skills not developing optimally. The research aimed to determine the feasibility of the product in terms of simplicity, ease of use, effectiveness, and efficiency, and to examine its contribution to students’ critical thinking skills. A research and development approach with the ADDIE model was employed. The product was validated by material experts (n=4) and media experts (n=5). Practicality was assessed through a teacher questionnaire (n=1) and student responses (n=23). Effectiveness was tested using a quasi-experimental design with experimental and control groups (each n=23) through pretest-posttest measures and statistical analyses (normality, homogeneity, independent samples t-test, and N-gain). The material expert validation reached 91.48% and media expert validation reached 93.97% (both very feasible). Teacher feasibility was 98.95% and student feasibility was 91.44% (very feasible). Critical thinking scores improved from a mean pretest of 57.7 to a mean posttest of 84.9. These findings confirm that the interactive material is highly feasible and effective for improving critical thinking in elementary science learning.